2012
DOI: 10.1111/j.1365-2966.2012.21583.x
|View full text |Cite
|
Sign up to set email alerts
|

Optical flux and spectral variability of blazars

Abstract: We report the results of optical monitoring for a sample of 11 blazars including 10 BL Lacertae objects (BL Lacs) and one flat spectrum radio quasar (FSRQ). We have measured the multiband optical flux and colour variations in these blazars on intraday and short-term time-scales of months and have limited data for two more blazars. These photometric observations were made during 2009-2011, using six optical telescopes, four in Bulgaria, one in Greece and one in India. On short-term time-scales we found signific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 149 publications
(226 reference statements)
1
60
0
1
Order By: Relevance
“…The observations were carried out at seven telescopes in Bulgaria, Greece, Georgia, and India. The telescopes and cameras that were involved in these observations are described in detail in Gaur et al (2012b).…”
Section: Optical Datamentioning
confidence: 99%
“…The observations were carried out at seven telescopes in Bulgaria, Greece, Georgia, and India. The telescopes and cameras that were involved in these observations are described in detail in Gaur et al (2012b).…”
Section: Optical Datamentioning
confidence: 99%
“…Alternatively, BL Lacs are often observed in bluer when brighter states, likely a result of significantly less radiative cooling of highly accelerated electrons off an under-luminous or non-existent accretion disk (Massaro et al 1998;Villata et al 2002;Vagnetti et al 2003;Gu & Ai 2011a;Gaur et al 2012). These observations have been extrapolated to represent the "typical" behavior of FSRQs and BL Lacs.…”
Section: Introductionmentioning
confidence: 99%
“…The colour or spectral behaviour of this blazar has been studied by number of authors (Ghisellini et al 1997;Raiteri et al 2003;Gu et al 2006;Rani et al 2010) on various timescales but is still a subject of debate. Some authors found a bluer-when-brighter (BWB) chromatism (e.g., Wu et al 2005;Gaur et al 2012); others claimed the opposite (e.g., Ghisellini et al 1997), or no colour change with brightness even in flaring state (e.g., Stalin et al 2006). Another intriguing result pointed out by Qian et al (1996) and Wagner et al (1996) is that the radio spectral index of this source was found to correlate with the intranight optical variations, thus giving further evidence for correlated variability in the radio and optical ranges as noted earlier by Quirrenbach et al (1991).…”
Section: Introductionmentioning
confidence: 99%